Adsorption of hydrogen arsenate and dihydrogen arsenate ions from neutral water by UiO-66-NH2. (1st October 2019) - Chang, Zu-Wei; Lee, Yu-Jen; Lee, Duu-Jong
Abstract: The metal-organic framework (MOF) UiO-66-NH2 was synthesized with different substrate to solvent ratios and its morphology, surface area, pore distributions, and NMR, XRD, and TGA-FTIR patterns were obtained. Adsorption tests at pH 7 and 25 °C showed that the produced UiO-66-NH2 has a hydrogen arsenate adsorption capacity of 76.9 mg/g. With the affinity onto Zr clusters, this MOF also can adsorb phosphate ions from water. Treatment with 1–4 M hydrochloric acid (HCl) protonated the amine groups in the MOF. Treatment with 1 M HCl at 25 °C for 6 h maximized the adsorption capacity of UiO-66-NH2 to 161.3 mg/g, such that the protonated amine groups accounted for 53.7% of the adsorption of arsenate from the water. The use of excessively strong acid at elevated temperature reduced the adsorption capacity. Highlights: Metal-organic framework (MOF) UiO-66-NH2 was synthesized and characterized. Adsorption capacity at pH 7 and 25 °C is 76.9 mg/g of hydrogen arsenate. 1M HCl treatment at 25 °C for 6 h increases adsorption capacity to 161.3 mg/g. Protonated amine groups accounts for enhanced adsorption of arsenate ions.